2021
DOI: 10.3389/fcvm.2021.707700
|View full text |Cite
|
Sign up to set email alerts
|

Management and 30-Day Mortality of Acute Coronary Syndrome in a Resource-Limited Setting: Insight From Ethiopia. A Prospective Cohort Study

Abstract: Background: Despite the fact that the burden, risk factors, and clinical characteristics of acute coronary syndrome (ACS) have been studied widely in developed countries, limited data are available from sub-Saharan Africa. Therefore, this study aimed at evaluating the clinical characteristics, treatment, and 30-day mortality of patients with ACS admitted to tertiary hospitals in Ethiopia.Methods: A total of 181 ACS patients admitted to tertiary care hospitals in Ethiopia were enrolled from March 15 to November… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…20 Heart failure and cardiogenic shock were seen in 9.09% and 6.36% of patients, respectively, findings consistent with those of Sidhu et al, 20 the ACCESS study, 22 and the CREATE registry. 23 The overall 30-day mortality rate in the present study was 5.82%, which was significantly lower as compared to a study by Fanta et al 31 The present study showed higher composite MACE in the STEMI subgroup in the 30-day outcome, similar to findings in the CREATE registry, which attributed poverty, affordability of treatment, and delayed access to hospitals to ACS-associated morbidity and mortality. 23 In the present study, the mortality rate was significantly higher among ACS patients with severe LV dysfunction (LVEF <30%), as observed in both in-hospital and 30day outcomes.…”
Section: Discussionsupporting
confidence: 74%
“…20 Heart failure and cardiogenic shock were seen in 9.09% and 6.36% of patients, respectively, findings consistent with those of Sidhu et al, 20 the ACCESS study, 22 and the CREATE registry. 23 The overall 30-day mortality rate in the present study was 5.82%, which was significantly lower as compared to a study by Fanta et al 31 The present study showed higher composite MACE in the STEMI subgroup in the 30-day outcome, similar to findings in the CREATE registry, which attributed poverty, affordability of treatment, and delayed access to hospitals to ACS-associated morbidity and mortality. 23 In the present study, the mortality rate was significantly higher among ACS patients with severe LV dysfunction (LVEF <30%), as observed in both in-hospital and 30day outcomes.…”
Section: Discussionsupporting
confidence: 74%
“…As the burden of AMI in sub-Saharan Africa continues to rise [40], there will be a growing need for research programs to monitor AMI care and implement interventions to maximize uptake of evidence-based care. To date, only a handful of published studies describe AMI care patterns in the region, and these studies have mostly been conducted at specialized cardiac centers with access to cardiologists and advanced coronary interventions [41][42][43]. Unfortunately, access to such advanced cardiac care is currently extremely limited in sub-Saharan Africa [44,45], and so the vast majority of AMI care is likely to occur in hospital settings like ours in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…Previous medical history, such as previous MI, and previous PCI was related to the ischemia risk of ACS patients, which predicted the occurrence of adverse events in such patients. In addition, several studies have demonstrated that systolic pressure, serum creatinine, and HDL played an important role in predicting the incidence of cardiovascular events ( 42 , 43 ). NT-proBNP was a sensitive indicator for evaluating the cardiac function of patients, which predicted the mortality of patients with ACS ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the LVEDD was also an important indicator reflecting the functional load of the cardiac pump, which also affected the prognosis of ACS patients ( 46 ). The Killip class and SYNTAX score reflected the cardiac function and complexity of coronary lesions, respectively, which were the determinants of the severity of ACS and also played an important role in predicting adverse outcomes ( 43 , 47 ). As for ACS patients with the muti-vessel disease, Iqbal et al ( 48 ) has demonstrated that the untreated proximal LAD (HR, 1.23; 95%CI, 1.06–1.51; P = 0.045) and RCA (HR, 1.36; 95%CI, 1.08–1.65; P = 0.007) were both associated with the increased mortality.…”
Section: Discussionmentioning
confidence: 99%